The Implications of the Global Minimum Tax on the Tax Strategies of Multinational Companies in Indonesia - Loso Judijanto (Nomico, 2025)
This study analyzes the implications of the Global Minimum Tax for the tax strategies of multinational enterprises operating in Indonesia. Using a mixed conceptual policy approach, the research integrates doctrinal analysis of the Global Anti-Base Erosion framework with an economic evaluation of multinational behavioral responses. The findings show that the Global Minimum Tax fundamentally reshapes incentives for profit shifting, tax arbitrage, and the use of preferential regimes. Multinational enterprises are expected to revise strategies related to intellectual property placement, intra-group financing, and transfer pricing as low-tax structures lose effectiveness under top-up tax mechanisms. For Indonesia, the policy impact is substantial: traditional tax incentives such as holidays and special economic zone benefits become less attractive, prompting a shift toward expenditure-based and non-tax incentives. The study further reveals that Indonesia must strengthen regulatory certainty, administrative capacity, and digital tax infrastructure to implement the Global Minimum Tax effectively. Strategic adjustments are also required in investment policy, emphasizing infrastructure quality, human capital, and institutional stability as key competitiveness drivers. The research concludes that the Global Minimum Tax presents both opportunities and challenges for Indonesia, offering potential revenue gains while demanding comprehensive structural reforms to maintain investment attractiveness and align with global tax standards.